Diffusion welding of stainless steel 304L/Monel K-500 composite materials produced with different methods. (19th June 2020) - Kejanli, Haluk
The stainless steel 304L (commercially supplied) and Monel K-500 that was prepared through cold pressing of metal matrix composite materials powder mixtures were joined by diffusion welding. Welding was performed under uniaxial compression using the 50 µm-thick nickel (Ni) and aluminum (Al) 2024 interlayers under 3 MPa at 950–980°C for 60 min in an argon gas atmosphere. After welding, the diffusion and intermediate zones of the samples were characterized using X-ray diffraction, optical microscopy, scanning electron microscopy, and energy-dispersive spectrometry analysis. As evaluating the diffusion zone with interlayer, it was determined that different interlayers expanded due to increasing temperature of the diffusion area. Interlayers expanded more on the K-500 side and relatively less on the 304L side. On the other hand, when samples with Ni interlayers were examined, high amount of Ni contained by both base material (304L) and interlayer led to the formation of rich Ni phases in the diffusion side. The brittle FeNi, Fe3 Ni2, CuNi, Cu9 Si, Cu0, 81 Ni0, 19, Fe0, 64 Ni0, 36, CrNi, Cr2 Ni3, FeNi3, FeCu4, and Al0.71 Cr0.3 Fe17.65, which were identified to form irregularity in the diffusion zone. These intermetallic phases increased the hardness and significantly decreased the ductility of different material couples joined by diffusion welding. As a result, the microhardness and lap shear tests were applied to specimens to characterize the mechanical properties of the joint zones. The maximum hardness and maximum lap shear values were obtained at joint that made with the Al interlayer at 980°C as 432.8 HV and 165 MPa.